A qualitative exploration of autistic mothers' experiences II: Childbirth and postnatal experiences. (July 2022) - Hampton, Sarah; Man, Joyce; Allison, Carrie; Aydin, Ezra; Baron-Cohen, Simon; Holt, Rosemary
Navigating childbirth and the postnatal period may pose additional challenges for autistic people, who can face communication and sensory barriers to accessing healthcare. However, research exploring autistic experiences of parenthood is scarce. Semi-structured interviews were conducted with 21 autistic and 25 non-autistic women 2–3 months after giving birth. Interviews concerned experiences of childbirth, postnatal healthcare and parenting. Thematic analysis revealed that sensory aspects of childbirth could be challenging for autistic participants; participants highlighted the need for sensory adjustments. Autistic participants stressed the importance of clear, direct communication from professionals during the birth. During childbirth and the postnatal period, autistic participants sometimes felt that professionals lacked knowledge of autism and this could hinder receiving appropriate adjustments. Both groups reported several parenting strengths and challenges. The findings indicate ways in which childbirth and postnatal healthcare can be improved for autistic people, including sensory and communication adjustments. They also indicate a need for greater autism-related training for professionals involved in childbirth and postnatal care. Lay abstract: Very little research has looked at how autistic people experience childbirth and the first few months of parenthood. We interviewed 21 autistic and 25 non-autistic women 2–3 months after their baby was born, to find out how they experienced giving birth and being a parent. Some autistic participants found sensory aspects of giving birth difficult, such as noise and being touched. They also wanted healthcare professionals to give them clear information while giving birth. Participants sometimes thought that healthcare professionals did not know enough about autism. Autistic and non-autistic participants both found parenthood difficult at times and autistic parents sometimes had extra difficulties, such as with planning and organising. Autistic participants also felt good at understanding their baby's needs. This research suggests that autistic people would benefit from changes to childbirth and postnatal healthcare such as being communicated with more clearly. It also indicates that healthcare professionals should receive more training about autism.